Populist leadership and collective action in Latin America - Durán Migliardi, Carlos (Revista de Historia Social y de las Mentalidades, 2025)
Populist leadership has been a phenomenon of recurring mention in Latin America. At different times, his allusion to the vocabulary of the social sciences appears as a warning that, even when there is not total clarity regarding its characteristics, it constitutes a "threat" to the constitution of stable democratic societies in the region. And, however, which to ghost, the populism constantly reemerges. What are the causes of such recurrence? In this text we intend to offer a summary approach to the relationship between the phenomenon of populist leadership and the dynamics of collective action, stating that probably -and contrary to the usual conceptions on this topic- the populist recurrence can well be explained, by a partly, due to its high capacity for articulation with the elements that make up collective action and, on the other, due to the increasingly visible demand to broaden the possibilities of politics and democracy.
Keywords: populism; collective action; politics